A Novel Multi-Hop Clustering Routing Algorithm Based on Particle Swarm Optimization for Wireless Sensors Networks - Xiuwu, Yu; Zixiang, Zhou; Wei, Peng; Yong, Liu (Wireless personal communications, 2023)
Since wireless sensor network have a finite amount of energy, lowering network energy consumption and prolonging the life of the network are essential considerations for WSN applications. A novel multi-hop clustering routing algorithm based on particle swarm optimization was suggested to address the problem of existing routing algorithms' short network life. Formerly, the most suitable cluster head was chosen by taking into account the energy of sensor nodes, the distance between nodes in the cluster, the distance between cluster head and BS, and other factors during the cluster head selection stage. Second, a relay node selection mechanism is proposed during the data transmission stage. Finally, to decrease energy usage, the energy threshold re-clustering scheme is employed. In comparison to POFCA, LEACH, and EEUC, simulation experiments show that the EBPSO algorithm enhances network lifetime by 1.7 percent, 24.7 percent, and 9.2 percent, respectively.